Friction Stir Welding Simulation of AA6061-T6 Aluminum Alloy: A SolidWorks-based investigation of lap joint configuration - Nedal Musbah Almeraash; Omar Ahmed Edbeib (African Journal of Advanced Pure and Applied Sciences, 2025)
This study presents a detailed simulation-based investigation of Friction Stir Welding (FSW) applied to AA6061-T6 aluminum alloy in a lap joint configuration, utilizing SolidWorks Simulation. Two 150×50×6 mm plates, overlapped by 25 mm, were welded using typical FSW parameters. The simulation revealed a peak temperature of 470°C, significantly below the alloy’s melting point, confirming solid-state welding. Mechanical analyses showed a safe von Mises stress of 137 MPa, an ultimate tensile strength of 240 MPa (77% of the base material), and minimal deformation of approximately 0.18 mm. These outcomes demonstrate FSW’s ability to produce strong, defect-free joints without melting and validate SolidWorks as a reliable tool for simulating heat flow and stress distribution in the FSW process.